Review paper UVA1 phototherapy in dermatological treatment - Malinowska, Karolina; Sysa-Jędrzejowska, Anna; Woźniacka, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Literature data indicate the beneficial therapeutic effect of UVA1 irradiation, whose biological properties are significantly different from those of other UV light waves, which is connected with their deeper penetration into the skin. Taking into account immunomodulatory mechanisms of UVA1 action, which mostly influences the apoptosis of fibroblasts, mast cells, Langerhans cells, and T lymphocytes, UVA1 radiation is indicated in the treatment of four major groups of skin diseases: T-cell and mast-cell mediated skin diseases, connective tissue diseases, and dermatoses in HIV positive patients sensitive to phototherapy. This publication presents a review of the literature concerning indications for UVA irradiation, recommended doses, as well as the most often observed adverse events.